Professional Support After Partner Loss: Likelihood and Correlates of Help-Seeking Behavior - Jopp, Daniela S.; Lampraki, Charikleia; Meystre, Claudia; Znoj, Hansjörg; Brodbeck, Jeannette (Frontiers in Psychology, 2021)
Intimate partner loss in later life can be one of the most stressful events in adulthood. Individuals who struggle to adapt to the new life conditions may need support from a mental health professional. However, little is known about the likelihood to seek professional help after separation, divorce or bereavement in later life and associated factors. This study investigated Professional Help Seeking (PHS) for partner loss after long-term marriages in separated, divorced and bereaved individuals and examined the extent to which specific person and event-related variables, as well as depressive symptoms increase its likelihood. Data were derived from the LIVES "Intimate Partner Loss Study". Self-administered questionnaires were completed by 388 adults. PHS was higher after separation (57%) and divorce (49%), compared to widowhood (18%). Higher PHS likelihood was associated with separation and divorce, female gender, having someone to count on, loss unexpectedness, needing more time to overcome loss and more depressive symptoms. Informing individuals unlikely to seek help (e.g., males, bereaved, individuals with no confidant) about PHS benefits may facilitate adaptation to partner loss.